BIOLOGIA DE Panonychus ulmi (KOCH, 1836) (ACARI: TETRANYCHIDAE) EM MACIEIRA - Kovaleski, AdalÃ©cio; Vendramim, JosÃ© Djair (REVISTA DE AGRICULTURA, 2015)
BIOLOGIA DE Panonychus ulmi (KOCH, 1836) (ACARI: TETRANYCHIDAE) EM MACIEIRA